Direito fundamental à privacidade versus poder diretivo do empregador: os limites de uso dos dados de geolocalização pelo empregador - Santos, Raphael Felipe da Silva (2024)
This master's thesis addresses the theme of the limits of employee geolocation tracking in light of personality rights and the application of the General Data Protection Law (LGPD). The study is divided into four chapters. It begins with an examination of fundamental and privacy rights. Following this, data control methods are explored, detailing their characteristics, advantages, and disadvantages, and reviewing the regulations on remote work introduced in the CLT (Consolidation of Labor Laws). Additionally, without intending to conduct a comparative law study, regulations from the ILO related to the monitoring of remote employees are presented. Finally, the General Data Protection Law (LGPD) and its application to employees are analyzed, focusing on its foundations, principles, and legal bases for the processing of personal and sensitive personal data. Among the conclusions, it is noted that the rules introduced into the Brazilian legal system by the LGPD impose new limits on employers regarding employee monitoring, especially due to the right to informational self determination, the impossibility of using consent as a legal basis for processing employees' personal or sensitive data, the requirement to specify purposes for processing such data, and adherence to the necessity principle (also called minimization). Thus, it is also understood that there is a need to revise existing interpretations of certain monitoring practices, examining them in the light of the LGPD's introduced norms. The research approach is carried out through the deductive method, based on national and international bibliographic research and documentary analysis, drawing on national regulations, those of the ILO and the European Union, as well as jurisprudential research